Jira 7 guide for administrators and developers - Sagar, Ravi (Packt, 2018)
"This course will show you how to use and manage your Atlassian JIRA instance. It will begin with the basics of JIRA and show how JIRA can be customized to suit the needs of your organization. This updated edition will cover all major components of JIRA 7, which includes JIRA Software, JIRA Core, and JIRA Service Works. We cover everything you need to know to set up a fully-functional implementation. Finally, we will also go over the newly added features in Jira 7.10"--Resource description page